Para aumento da instrução da mocidade da nossa pátria: estratégias de difusão do letramento na Vila de São João Del Rei (1824-1831) - Christianni Cardoso Morais (2002)
The objective of this work is to understand the origins, use and circulation of written works in the Vila de São João del-Rei, between 1824 and 1831, through the projects of constituition of the first public library of the province of Minas Gerais and of a readers society called Sociedade Phylopolytechnica. The attempts to create these institutions make sense when placed in their context of an extremely active urban centre at the moment in which the elites of the recently independent Brazil gradually rejected the Lusitanian values and sought to constitute a new nation. The Biblioteca and the Sociedade Phylopolytechnica, identified as nongovernmental public meeting places or social loci of ideas, can be taken as exemplary cases of the civilizing process occurring in Brazil, principally because the expansion of the use of written works among the free and wealthy had in view the development of norms and values that the elites identified as those of civilized European countries.